“ICODE Hip US Calculator”: a mobile phone aid for screening with Graf’s sonographic technique - Chlapoutakis Konstantinos; O’Beirne Joseph; Dubs Beat; Maizen Claudia; Placzek Sonja; Tzatzairis Themistoklis; Casini Carolina (Journal of Ultrasonography)
Aiming to offer a diagnostic tool to aid examiners with correct hip typing and decision-making about patient management, members of the Board of the International Interdisciplinary Consensus Committee on DDH Evaluation (ICODE – https://www.icode.expert), introduced the cross-platform mobile application (Android and iOS) called “ICODE Hip US Calculator”.